Essential urology : a guide to clinical practice - Potts, Jeannette M. (Current clinical urology., 2012)
Extensively revised and updated, the second edition of Essential Urology: A Guide to Clinical Practice provides support to primary care physicians through its review of common genitourinary problems. This edition continues to provide the primary care physician with tools to better recognize urological diseases as well as updated management strategies for these disorders. To enhance the theme of comprehensive care and family medicine, the volume is formatted according to the life cycle and the urological challenges, which may be detected and diagnosed by primary care physicians respective of the patient's stage in life, beginning with pregnancy and in utero diagnoses. Pediatric themes such as infection and voiding dysfunctions are followed by adult urological topics ranging from prostate diseases, nephrolithiasis, overactive bladder syndromes, incontinence and urological cancer screening. Three new chapters are added addressing male infertility/andrology and the growing demand for integrative and alternative medical care of urologic patients, as well as commonly encountered dermatological problems in the genital area. Essential Urology: A Guide to Clinical Practice, Second Edition is extremely comprehensive and yet, very accessible. It is authored by experts representing the spectrum of urological subspecialties, further enhancing the value of this unique work.